Building The STEM Village: an interview on fostering LGBTQ+ visibility and community (Communications Biology, 2022)
The STEM Village is an international effort dedicated to improving the visibility of the LGBTQ+ STEM community. As part of our own celebration of LGBTQIA+ STEM Day, we spoke to members of The STEM Village leadership team about their programming and ways to get involved.